Acquired Haemophilia A in four north European countries: survey of 181 patients. (21st December 2022) - Lindahl, Rickard; Nummi, Vuokko; Lehtinen, Anna‐Elina; Szanto, Timea; Hiltunen, Leena; Olsson, Anna; Glenthoej, Andreas; Chaireti, Roza; Vaide, Ines; Funding, Eva; Zetterberg, Eva
Summary: Acquired haemophilia A (AHA) is a rare bleeding disorder caused by acquired antibodies against coagulation factor VIII. In the Nordic countries, treatment and outcomes have not been studied in recent times. To collect retrospective data on patients diagnosed with AHA in the Nordic countries between 2006 and 2018 and compare demographic data and clinical outcomes with previously published reports, data were collected by six haemophilia centres: three Swedish, one Finnish, one Danish and one Estonian. The study included 181 patients. Median age at diagnosis was 76 (range 5–99) years, with even gender distribution. Type and severity of bleeding was comparable to that in the large European Acquired Haemophilia Registry study (EACH2). Bleedings were primarily treated with activated prothrombin complex concentrate (aPCC) with a high success rate (91%). For immunosuppressive therapy, corticosteroid monotherapy was used most frequently and this may be the cause of the overall lower clinical remission rate compared to the EACH2 study (57% vs. 72%). Survey data on 181 patients collected from four north European countries showed similar demographic and clinical features as in previous studies on AHA. aPCC was used more frequently than in the EACH2 study and the overall remission rate was lower.